Risk of hepatocellular carcinoma in relation to ABO blood type. Issue 1 (January 2016) - Iavarone, Massimo; Della Corte, Cristina; Pelucchi, Claudio; Marconi, Maurizio; Trotti, Roberta; Triolo, Michela; Manini, Matteo Angelo; La Vecchia, Carlo
Abstract: Background: Mortality and incidence rates of hepatocellular carcinoma (HCC) parallel the geographical distribution of hepatitis B and C viruses among the general population, however genetic factors modulate individual cancer risk. Aims: ABO blood type, as a genetic marker, has previously been associated with the risk of several malignancies; we aimed to evaluate whether an association exists with HCC. Methods: This is a retrospective case-control study based on ABO distribution in 194 patients with HCC, compared with 215 decompensated cirrhotics without HCC listed for liver transplantation, and 90, 322 healthy blood donors. Results: In patients with HCC, prevalence of blood type O was 35%, vs. 44% in cirrhotics (OR: 0.67, 95% CI 0.45–0.99; p  = 0.046) and 45% in blood donors (OR: 0.65, 95% CI 0.48–0.88; p  = 0.004). Conclusions: ABO blood type non-O is associated with higher risk of hepatocellular carcinoma, compared to cirrhotics without HCC and healthy subjects.